Influence of Product and Price on Electric Motorcycle Purchases in Pontianak - Dio Suhadi; Sumiyati Sumiyati (Penerbit Goodwood, 2026)
Purpose: This study aims to evaluate the influence of price and product characteristics on consumers’ decisions to purchase electric motorbikes at CV Sinergi Grafika Perkasa in Pontianak City. Methodology: An associative study design was employed, with 117 respondents selected using saturation sampling. Data were analyzed using multiple linear regression, the multiple correlation coefficient (R), the coefficient of determination (R²), an F-test (Simultaneous Test), and a t-test (Partial Test). Results: The regression equation obtained was Y = 2.33 + 0.123X1 + 0.496X2. The multiple correlation coefficient (R) of 0.992 indicates a very strong relationship between product and price in the decision to purchase electric motorbikes. The coefficient of determination (R²) was 0.983, indicating that the variables explained 98.3% of the variance in purchasing decisions, with the remaining 1.7% attributed to external factors not explored in this study. The F test revealed that both price and product characteristics simultaneously influenced the purchasing decision. The t-test showed that while price did not significantly impact the decision to purchase, product characteristics had a significant partial effect. Conclusions: This study highlights the critical role of product characteristics in purchasing decisions, suggesting a shift in consumer preferences towards product value over price, particularly for eco-friendly products. Limitations: This study was limited by the exclusion of external factors that could also influence purchasing decisions. Contributions: This study provides insights for marketing strategies, particularly for promoting environmentally friendly products in local markets.